Impact of oil waste discharge from Al-Nassiriya oil refinery upon physical chemical properties and heavy elements content of vicinity soil - Bassim y. AL-khafaji ,; Noora Q. Kareem, (University of Thi-Qar Journal of Science, 2021)
The present study attempt to know the impact of oil waste discharge from Al-Nassiriya oil refinery upon some  physical chemical properties and heavy elements  (HEs) concentration  in the vicinity soil , during the period from  January until August  2020 . Some physical and chemical factors were measured also selected HEs ( Co , Ni , Pb and V ) concentration in the soil were measured by using Flam Atomic Absorption  Spectrometry ( FAAS ) , in addition to soil texture and total organic carbon content were measured as percentage . The results revealed that the range of the soil parameters were ,  Temp.(16.3 – 44.3) ◦c , pH (6.0 - 8.7) , electrical conductivity E.C. (119.2-312.10) µs/cm  , salinity (0.02 - 1.63) gm/kg , porosity (29 – 58) % ,  NO3 (7.91 - 97.5) mg /kg , PO4 (5.4 - 24.7) mg/ kg , SO4 (480 - 1739) mg/kg , while soil texture was silty clay at st.1 and st.2 , sandy loam at st.3 and silty loam at st.4 . Total organic carbon  (TOC %) content and organic matter (OM%) were ranged from (3.89  - 17.52) % and (2.26 – 10.16) % respectively . HEs content in the soil of study  were ranged from Pb (5.9  - 63.7 ) , Co (4.7  -  51.77) , V (36  - 181 ) and Ni (5.57  - 222 ) mg/kg  dry weight respectively .